The synergistic effect of Lactobacillus plantarum CCFM242 and zinc on ulcerative colitis through modulating intestinal homeostasis. Issue 9 (9th September 2019) - Zhai, Qixiao; Zhang, Qingsong; Tian, Fengwei; Zhao, Jianxin; Zhang, Hao; Chen, Wei
Abstract : Zn-enriched Lactobacillus plantarum treatment protects intestinal barrier and immune function and alleviates colitis in mice. Abstract : The beneficial effects of the essential metal zinc (Zn) and probiotics on gut health have been well documented, but how they synergistically affect intestinal physiology is not thoroughly understood. In this study, the Zn-enriching ability of 33 probiotics in a medium or an aqueous solution was evaluated. A Lactobacillus plantarum strain, CCFM242, with a superior Zn-enriching ability was screened. Among the cellular components, the cell wall played the most important role in the Zn binding of L. plantarum CCFM242. The carboxyl and amino groups on the surface of the strain were also vital for Zn enrichment. Upon optimization of the Zn-enriching procedure, the Zn-binding ability of this strain reached 24.89 ± 0.50 mg g −1 dry biomass. Compared to the treatment of ZnSO4 or L. plantarum CCFM242, oral supplementation with Zn-enriched L. plantarum CCFM242 resulted in a higher serum Zn level, enhanced levels of mRNA expression of colonic tight junctions, increased levels of short-chain fatty acids (SCFAs) in colonic contents, and stronger modulatory effects on the anti-oxidant and immune defense systems in the gut of normal mice. Zn-Enriched L. plantarum CCFM242 treatment also offered more significant protective effects against dextran sodium sulfate (DSS)-induced colitis in mice compared to the treatment of ZnSO4 or L. plantarum CCFM242 alone. The synergistic effect of Zn-enriched L. plantarum CCFM242 may be due to the increased tolerance of the strain to the gastrointestinal tract conditions and the higher bioavailability of Zn after the metal-enrichment process.